Accuracy of Humeral Implant Positioning Using a Canal-Sparing Total Shoulder Arthroplasty System. (April 2019) - Baranek, Eric S; Trofa, David P; Levine, William N; Goldberg, Steven S
Background: Accurate restoration of anatomy is critical in reestablishing proper glenohumeral joint function in total shoulder arthroplasty (TSA). However, even experienced surgeons inconsistently achieve anatomic restoration. This study evaluates whether a new canal-sparing arthroplasty system, designed using the principles of calibrated bone resection and incorporating a nonspherical humeral head prosthesis, can assist in more accurate and reliable reproduction of proximal humeral anatomy compared to a stemmed arthroplasty system. Methods: The difference between the anatomic center of rotation (COR) of the humeral head and the postoperative prosthetic COR (defined as ΔCOR) was measured in a consecutive case series of 110 shoulder arthroplasties performed by a single surgeon. The first 55 cases used a stemmed arthroplasty system and the subsequent 55 cases used a new canal-sparing implant system that uses a multiplanar osteotomy (MPO) during humeral head preparation. Cases with ΔCOR ≥3.0 mm were deemed clinically significant outliers. Results: The average ΔCOR in the MPO group was 1.7 ± 1.2 mm versus 2.8 ± 1.5 mm in the stemmed group ( P = .00005). The incidence of outliers was lower (14.5% vs 40.0%, P = .005), and there were more cases with a ΔCOR ≤1.0 mm (32.7% vs 3.6%, P = .0001) in the MPO group compared to the stemmed group. Conclusion: The MPO TSA system provided improved accuracy and precision in restoring proximal humeral anatomy compared to stemmed arthroplasty systems, even in its initial use. This alternative method of humeral replacement may increase consistency in restoring proper anatomy and kinematics in TSA.